2018
DOI: 10.1111/famp.12361
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Model Predicting Self‐Concept in Pediatric Chronic Illness

Abstract: Although self-concept has been identified as salient to the psychosocial adjustment of adolescents dealing with a chronic illness (CI), little research has focused on its predictors it. Given that depression and parent-child attachment have been linked to self-concept in the population at large, the goal of this study was to evaluate these relationships longitudinally in a sample of adolescents with CI. Using participant data from the Mastering Each New Direction (MEND) program, a 3-month psychosocial, family … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Nonetheless, results from studies with older subjects generated important knowledge that might also apply to younger children. Emerson et al (2019) found that decreases in depressive symptoms were linked to increases in self-concept in adolescents with a chronic illness that participated in a psychosocial, family based intensive outpatient program. Chavez-Hernandez et al (2018) reported that self-evaluation and family self-concept were associated with depression in middle to late childhood.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, results from studies with older subjects generated important knowledge that might also apply to younger children. Emerson et al (2019) found that decreases in depressive symptoms were linked to increases in self-concept in adolescents with a chronic illness that participated in a psychosocial, family based intensive outpatient program. Chavez-Hernandez et al (2018) reported that self-evaluation and family self-concept were associated with depression in middle to late childhood.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we measured the feasibility of collecting repeated measures data, with CMC caregivers at high participant attrition risk during the onset of a pandemic. Despite this, the study's overall 31% attrition rate was similar to a pre‐pandemic study of caregivers of children with chronic health conditions reporting a 30% attrition rate over 60 days (Emerson et al, 2019). One possible explanation the study team had for the 31% attrition in this study is related to offering paper surveys during enrolment of the first 15 caregivers.…”
Section: Discussionmentioning
confidence: 62%
“…Despite this, the study's overall 31% attrition rate was similar to a T A B L E 7 Community healthcare supports. pre-pandemic study of caregivers of children with chronic health conditions reporting a 30% attrition rate over 60 days (Emerson et al, 2019). One possible explanation the study team had for the 31% attrition in this study is related to offering paper surveys during enrolment of the first 15 caregivers.…”
Section: Retentionmentioning
confidence: 99%